2006
DOI: 10.1177/089686080602600317
|View full text |Cite
|
Sign up to set email alerts
|

Peritoneal Injury by Methylglyoxal in Peritoneal Dialysis

Abstract: Background Peritoneal dialysis (PD) is a common treatment for patients with reduced or absent renal function. Long-term PD leads to peritoneal injury with structural changes and functional decline, such as ultrafiltration loss. At worst, peritoneal injury leads to encapsulating peritoneal sclerosis, a serious complication of PD. Glucose degradation products contained in PD fluids contribute to the bioincompatibility of conventional PD fluids. Methylglyoxal (MGO) is an extremely toxic glucose degradation produc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
61
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 59 publications
(68 citation statements)
references
References 32 publications
6
61
1
Order By: Relevance
“…This creates difficulty in interpretation of such results because MGO levels among MHs can vary considerably . Similar to previous in vivo studies, tissue damage increased proportionally to MGO concentrations, reflecting its toxic nature. A wealth of in vitro literature currently describes potential mechanisms of MGO toxicity, including free radical production, enzyme dysfunction, oxidative stress, and DNA damage .…”
Section: Discussionsupporting
confidence: 57%
See 2 more Smart Citations
“…This creates difficulty in interpretation of such results because MGO levels among MHs can vary considerably . Similar to previous in vivo studies, tissue damage increased proportionally to MGO concentrations, reflecting its toxic nature. A wealth of in vitro literature currently describes potential mechanisms of MGO toxicity, including free radical production, enzyme dysfunction, oxidative stress, and DNA damage .…”
Section: Discussionsupporting
confidence: 57%
“…The effects of translation to in vivo models are less clear, with several studies reporting differing outcomes. One such study applying MGO to rat peritoneum found dense adhesion formation and animal death at 20 mmol/L (1.44 mg/mL) levels of MGO . Interestingly, we report no changes to sinus mucosa at similar levels and only microscopic changes at more than double this concentration.…”
Section: Discussioncontrasting
confidence: 56%
See 1 more Smart Citation
“…This concentration is approximately 10 000 times its concentration in conventional dialysates (13,25). Studies have shown that dialysate loading with up to 20 mmol/L of MG is required to induce full-scale morphological changes in the mesenterium by 21 days of daily dialysis in rats (25)(26)(27). Thus designed our experimental settings induced typical PD-associated morphological alterations of the peritoneum, and oral PM had no effects on pentosidine accumulation in the mesenterium or dialysate effluent despite the fact that PM crossed the peritoneum and amounted to some 20 μg/mL in the dialysate effluent.…”
mentioning
confidence: 89%
“…In patients undergoing PD, MMP‐2 levels in the peritoneal effluent are associated with peritoneal injury and reflect the peritoneal solute transport rate . In experimental models, MMP‐2 levels in drained dialysates became significantly elevated with the development and progression of peritoneal injury, reflected by increased peritoneal solute transport rates . It has been reported that the MMP inhibitor ONO‐4817 prevents peritoneal injury in rats .…”
Section: Introductionmentioning
confidence: 99%